Hepatitis B virus promotes its own replication by enhancing RAB5A-mediated dual activation of endosomal and autophagic vesicle pathways - Zhenyu Zhao; Zhen Wei; Jiaxin Zheng; Zhihong Li; Hecun Zou; Xiang Wen; Fahong Li; Xueyu Wang; Qian Huang; Huaqing Zeng; Hui Fan; Xuefei Cai; et al. (Emerging Microbes and Infections)
Chronic hepatitis B virus (HBV) infection remains one of the major global public health concerns, and it develop into liver fibrosis, cirrhosis, and hepatocellular carcinoma. Recent evidence suggests that endosomal and autophagic vesicles are beneficial for HBV replication. However, it has not been well elucidated how HBV exploits such intracellular vesicle systems for its replication. RAB5A, a member of small GTPase family, plays crucial roles in early endosome biogenesis and autophagy initiation. We observed that RAB5A mRNA and protein levels were significantly increased in HBV-expressing hepatoma cell lines as well as in liver tissue samples from chronic HBV-infected patients. Moreover, RAB5A silencing inhibited HBV replication and subviral particle (SVP) expression significantly in HBV-transfected and -infected hepatoma cells, whereas RAB5A overexpression increased them. Mechanistically, RAB5A increases HBV replication through enhancement of early endosome (EE) – late endosome (LE) activation by interacting with EEA1, as well as enhancing autophagy induction by interacting with VPS34. Additionally, HBV infection enhances RAB5A-mediated dual activation of EE-LE system and autophagy. Collectively, our findings highlight that HBV utilizes RAB5A-mediated dual activation of endosomal and autophagic vesicle pathways for its own replication and persistence. Therefore, RAB5A is a potential target for chronic HBV infection treatment.